2017
DOI: 10.3389/fimmu.2017.00190
|View full text |Cite
|
Sign up to set email alerts
|

Specific and Efficient Uptake of Surfactant-Free Poly(Lactic Acid) Nanovaccine Vehicles by Mucosal Dendritic Cells in Adult Zebrafish after Bath Immersion

Abstract: Activation of mucosal immunity is a key milestone for next-generation vaccine development. Biocompatible polymer-based nanoparticles (NPs) are promising vectors and adjuvants for mucosal vaccination. However, their in vivo uptake by mucosae and their biodistribution in antigen-presenting cells (APCs) need to be better understood to optimize mucosal nanovaccine designs. Here, we assessed if APCs are efficiently targeted in a spontaneous manner by surfactant-free poly(lactic acid) nanoparticles (PLA-NPs) after m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…Mammalian macrophages and dendritic cells play an important role in antigen transportation. Rességuier et al ( 43 ) showed that dendritic cells take up surfactant-free poly (lactic acid) nanoparticles in the gill epithelium. In the present work, numerous gill epithelium-resident macrophage/DC-like GAS cells that contained bacterin were found following bath vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian macrophages and dendritic cells play an important role in antigen transportation. Rességuier et al ( 43 ) showed that dendritic cells take up surfactant-free poly (lactic acid) nanoparticles in the gill epithelium. In the present work, numerous gill epithelium-resident macrophage/DC-like GAS cells that contained bacterin were found following bath vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies in Atlantic salmon and rainbow trout (Oncorhynchus mykiss) demonstrated the presence of T lymphocytes embedded in a meshwork of reticulated epithelial cells in ILT. Only few immunoglobulin (Ig)M+ lymphocytes were detected, but the structure appears rich in cells expressing major histocompatibility complex (MHC) class II+ cells and IgT transcripts [12][13][14][15][16][17][18][19][20]. The ILT must be considered as a part of the gill-associated lymphoid tissue (GIALT), which is defined as one of the four main mucosal immune compartments found in bony fish [21].…”
Section: Introductionmentioning
confidence: 99%
“…Delivery vehicles investigated in zebrafish include single-walled carbon nanotubes (SWCNTs), nanoliposomes and biocompatible non-toxic approved materials, such as polymer-based nanoparticles [e.g. poly(lactic acid) (PLA) or poly(lactic-co-glycolic acid) (PLGA)] and other polymers (Zhang et al, 2020;Crecente-Campo et al, 2019;Ji et al, 2019;Guo et al, 2018;Lovmo et al, 2017;Resseguier et al, 2017;Ruyra et al, 2014). Studies in both adult and larval zebrafish have demonstrated that nanoparticles can cross the tissue epithelium and be taken up by antigenpresenting cells (Zhang et al, 2020;Resseguier et al, 2017) and other leukocytes (Lovmo et al, 2017).…”
Section: Zebrafish As a Model For Vaccine Deliverymentioning
confidence: 99%
“…poly(lactic acid) (PLA) or poly(lactic-co-glycolic acid) (PLGA)] and other polymers ( Zhang et al, 2020 ; Crecente-Campo et al, 2019 ; Ji et al, 2019 ; Guo et al, 2018 ; Lovmo et al, 2017 ; Resseguier et al, 2017 ; Ruyra et al, 2014 ). Studies in both adult and larval zebrafish have demonstrated that nanoparticles can cross the tissue epithelium and be taken up by antigen-presenting cells ( Zhang et al, 2020 ; Resseguier et al, 2017 ) and other leukocytes ( Lovmo et al, 2017 ). Crecente-Campo et al (2019) , in turn, have investigated the effect of particle size on phagocytosis and antigen presentation by macrophages.…”
Section: Modelling Tb Vaccine Development In Zebrafishmentioning
confidence: 99%